A nucleoside-sparing regimen of dolutegravir plus ritonavir-boosted atazanavir in HIV-1-infected patients with virological failure: the DOLATAV study - Spagnuolo V; Galli L; Poli A; Bigoloni A; Fumagalli L; Gianotti N; Nozza S; Ferrari D; Locatelli M; Lazzarin A; Castagna A (Dove Medical Press, 2019)
Vincenzo Spagnuolo,1,2 Laura Galli,2 Andrea Poli,2 Alba Bigoloni,2 Luca Fumagalli,2 Nicola Gianotti,2 Silvia Nozza,2 Davide Ferrari,3 Massimo Locatelli,3 Adriano Lazzarin,2 Antonella Castagna1,2 1Vita-Salute San Raffaele University, Faculty of Medicine and Surgery, Milan, Italy; 2Clinic of Infectious Diseases, Istituto di Ricerca e Cura a Carattere Scientifico (IRCCS) San Raffaele Scientific Institute, Milan, Italy; 3Laboratory Medicine Service, IRCCS San Raffaele Hospital, Milan, Italy  IntroductionThe increased exposure of dolutegravir (DTG) when given with atazanavir/ritonavir (ATV/r), as well as the acceptable safety profile, may suggest the use of this combination as a two-drug regimen both in virologically suppressed and treatment-failing subjects.1–5  This nucleoside reverse transcriptase inhibitors (NRTIs)-sparing regimen, characterized by a high genetic barrier, may represent an option in patients who have failed previous regimens and developed pharmacoresistance mutations to NRTIs and nonnucleoside reverse transcriptase inhibitors (NNRTIs).  However, no data on DTG plus boosted ATV in patients with virological failure are currently available.  Therefore, the aim of the DOLATAV study was to investigate the efficacy, safety, and pharmacokinetics of ATV/r 300/100 mg once-daily plus DTG 50 mg once-daily